2022
DOI: 10.1177/21582440221093354
|View full text |Cite
|
Sign up to set email alerts
|

How Transformational Leaders Are Engaged in Work Settings During Episode of Covid-19? Exploring Mediating Effects of Structural Empowerment and Process Innovation

Abstract: In this modern world with the growing trend of globalization, cultural and environmental changes, and the increased pace of technological advancements, new challenges have appeared in a tremendous manner. In the wake of these recent trends and complexities alongside the worldwide pandemic (COVID-19), organizations are working to provide a self-motivated and highly engaging environment for employees. The study intends to explore the relationship between Transformational Leadership (TFL) and Work Engagement (WE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…For instance, Islam and colleagues (2020) demonstrated the pivotal role of leaders in supporting employees’ adaptive behaviors in rapidly changing and unstable environments. Similarly, Khan and colleagues (2022) stressed the importance of fostering balanced leader–follower relationships to enhance adaptability in an era characterized by globalization, cultural shifts, and technological advancements. Nonetheless, this dynamic may vary in work contexts characterized by constant change and unpredictability, such as the ongoing aftermath of the COVID-19 pandemic, which highlighted deficiencies in leadership during crises (Khan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Islam and colleagues (2020) demonstrated the pivotal role of leaders in supporting employees’ adaptive behaviors in rapidly changing and unstable environments. Similarly, Khan and colleagues (2022) stressed the importance of fostering balanced leader–follower relationships to enhance adaptability in an era characterized by globalization, cultural shifts, and technological advancements. Nonetheless, this dynamic may vary in work contexts characterized by constant change and unpredictability, such as the ongoing aftermath of the COVID-19 pandemic, which highlighted deficiencies in leadership during crises (Khan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Khan and colleagues (2022) stressed the importance of fostering balanced leader–follower relationships to enhance adaptability in an era characterized by globalization, cultural shifts, and technological advancements. Nonetheless, this dynamic may vary in work contexts characterized by constant change and unpredictability, such as the ongoing aftermath of the COVID-19 pandemic, which highlighted deficiencies in leadership during crises (Khan et al, 2022). In contemporary environments marked by perpetual pressure to modernize processes and routines, having a less effective leader seems to necessitate additional employee effort to independently adapt to uncertain circumstances, leading to heightened negative affective reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amid the height of the COVID-19 pandemic, the results of a recent study adopted by Santoso et al [ 70 ] indicate that TLS played a key role in strengthening EEG via internal communication, which in turn alleviated the concerns of employees regarding the COVID-19 pandemic. Similarly, another study aimed at determining to what extent TLS engages the workplace setting among Pakistani bankers during the height of the COVID-19 pandemic suggested that the workplace is more likely to be engaged by leaders who exhibit highly transformative leadership behaviors [ 71 ]. Additionally, transformational leadership theory suggests that transformational leaders can create a culture of engagement by instilling trust, providing meaningful work, providing resources to help employees stay focused, and recognizing employees’ contributions [ 72 ].…”
Section: An Overview Of the Theoretical Background And The Developmen...mentioning
confidence: 99%
“…For higher vocational colleges to adapt to the digital future, the support of technology is only a starting point. The key lies in whether they can develop next-generation technologies, the ability to narrow the talent pool gap, and the expertise to sustainably develop talent (Khan et al, 2022). Therefore, the goal of digital transformation lies in the transformation of talent, and the key lies in the transformation of talent development programs.…”
Section: Basic Principles For Higher Vocational Colleges To Deal With...mentioning
confidence: 99%